Pemanfaatan Lahan Tidur melalui Kegiatan Kebun Gizi di Desa Salut, Kecamatan Kayangan, Kabupaten Lombok Utara, Nusa Tenggara Barat - Muhammad Taufik Akbar; Anjas Madisha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Salut Village is one of the villages in Kayangan Sub-District, North Lombok District, West Nusa Tenggara. This village is located just below the foot of Mount Rinjani with a dry climate. On August 5, 2018 there was a 6.8 magnitude earthquake which destroyed almost everything in Salut Village. The impact is lack of food and medicine. LPPM IPB and HA-IPB sent facilitators on March 17 to respond to the disaster by providing program, namely nutrition garden activities. Nutrition garden was carried out in the East Salut hamlet by providing 1 ha of land and involving community members of the farmer group. There were 11 commodities planted, namely kale, Chinese cabbage, lettuce, spinach, long beans, chili, eggplant, tomatoes, bitter melon, sweet potatoes and cassava. The activities started from nursery, maintenance to harvesting were carried out by the community with the help of the facilitator.